Play Store Quranic Mushaf in Indonesia: Discourse on Digital Religious Text Authority, Variety and Standardization - Heriyanto Heriyanto (Religia, 2021)
This paper aims to see the development of the Play Store Al-Qur'an manuscripts in Indonesia as well as to question the discourse on the authority of digital religious texts. This study uses a field research model whose data are taken from various sources with observation, documentation, and interview techniques. The results of the study found that the Play Store Al-Qur'an manuscripts in Indonesia are quite varied and can be divided into three classifications: (1) Reading Mushaf; (2) Listening Mushaf; and (3) Learning Mushaf. Of the many mushaf applications available on the Play Store, only 10% said it had been approved by the LPMQ of the Ministry of Religion of the Republic of Indonesia, the rest did not mention a clear source. This phenomenon arises because of the lack of strict government supervision of digital Qur'anic mushaf and the absence of special treatment to suppress the circulation of digital Qur'ans that have not been standardized. This is at least influenced by the policy of digital Qur’anic standardization which has not been stated in PMA Number 44 of 2016 concerning Issuance, Standardization, and Circulation of Qur'anic Mushaf. As a result, the submission of digital Qur'an standardization at LPMQ while the rules are the same as printing manuscripts.